A dyadic perspective on coping and its effects on relationship quality and psychological distress in couples living with chronic pain: a longitudinal study - Mittinty, M. M. (2020)
Objective: Dyadic coping is a process of coping within couples that is intended not only to support the patient with chronic pain but also to maintain equilibrium in the relationship. This study aims to investigate the effect of patient-perceived and spouse-reported dyadic coping on both the patient and their partner's relationship quality and anxiety, stress, and depression over time. Methods: One hundred thirty-nine couples, with one partner experiencing chronic pain, participated in this study. Spanning three measurements over six months, couples reported on their anxiety, stress, depression, relationship quality, and dyadic coping. Results: Patient-perceived supportive dyadic coping was positively associated with both partners' relationship quality but was negatively associated with spouses' stress over time. Patient-perceived negative dyadic coping was negatively associated with both partners' relationship quality and positively associated with patients' depression and spouses' depression and stress over time. Spouse-reported supportive dyadic coping showed a positive association with their own relationship quality and a negative association with spouses' depression at baseline and patients' depression at three-month follow-up. Spouse-reported negative dyadic coping was negatively associated with their relationship quality at baseline and positively associated with their partner's anxiety and stress at six-month and three-month follow-up, respectively. Similar inference was observed from the findings of growth curve model. Conclusions: As compared with spouse report, patient perception of dyadic coping is a better predictor of both partners' relationship quality and psychological outcomes over time. Both partners may benefit from early psychosocial intervention to improve their dyadic coping, relationship quality, and psychological outcomes.